2014
DOI: 10.1063/1.4896167
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optical and electrical modeling of plasmon-enhanced thin film photovoltaics: A case-study on organic devices

Abstract: The nanoscale light control for absorption enhancement of organic photovoltaic (OPV) devices inevitably produces strongly non-uniform optical fields. These non-uniformities due to the localized optical modes are a primary route toward absorption enhancement in OPV devices. Therefore, a rigorous modeling tool taking into account the spatial distribution of optical field and carrier generation is necessary. Presented here is a comprehensive numerical model to describe the coupled optical and electrical behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…19,22 We have previously shown by a combined optical and electrical simulation of the device performance that NIR photocurrent enhancement can be achieved by using a metal nanograting as the back electrode. 16 Our simulations showed that excitation of SPPs in the grating enhances the optical field in the active layer and that the grating can be designed so that the enhancement occurs in the near-infrared where the normal absorption in the active layer is low. 16 Here we experimentally realize this device and demonstrate that enhancement of the EQE is indeed observed in the spectral region predicted by the simulation.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…19,22 We have previously shown by a combined optical and electrical simulation of the device performance that NIR photocurrent enhancement can be achieved by using a metal nanograting as the back electrode. 16 Our simulations showed that excitation of SPPs in the grating enhances the optical field in the active layer and that the grating can be designed so that the enhancement occurs in the near-infrared where the normal absorption in the active layer is low. 16 Here we experimentally realize this device and demonstrate that enhancement of the EQE is indeed observed in the spectral region predicted by the simulation.…”
Section: Introductionmentioning
confidence: 81%
“…16 Our simulations showed that excitation of SPPs in the grating enhances the optical field in the active layer and that the grating can be designed so that the enhancement occurs in the near-infrared where the normal absorption in the active layer is low. 16 Here we experimentally realize this device and demonstrate that enhancement of the EQE is indeed observed in the spectral region predicted by the simulation. This confirms the power of simulation to design gratings that target optical field enhancement in a specific wavelength range of interest that can be focused in the active layer.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations